Conceptualisation and conscience assessment in adolescence in forensic mental healthcare: experts’ perspectives - Tiemersma, J. (The journal of forensic psychiatry & psychology, 2022)
Child and adolescent psychology and psychiatry healthcare guidelines recommend a structured clinical assessment of conscience of juveniles displaying antisocial behaviour to substantiate the allocation of treatment or penal sanctions. The scientific literature on conscience development is accumulating, yet no widely accepted, integrative clinical instrument for assessment of conscience is available. Consequently, clinicians assess conscience, utilising their acquired knowledge and experience. Resulting in a largely intuitive process that varies vastly among professionals. This study aimed to gather and explicate the implicit knowledge of experienced clinicians on the assessment of adolescent conscience. Semi-structured interviews were conducted with seven clinical experts working in various Dutch (forensic) mental health organisations. Using a five-phase systematic and structured content analysis, the framework method was applied to explore the techniques and concepts used by clinical experts. The concepts they used grossly matched the concepts found in the literature. We identified three pivotal domains: empathic capacity, self-conscious emotions, and moral reasoning. Moreover, the data suggested to consider these domains expressing the overarching concept of self-image or identity. These results will enable the design of a clinically based, comprehensive instrument to improve the quality of the assessment of conscience in the context of child and adolescent forensic psychiatric healthcare.